2018
DOI: 10.1111/ppl.12862
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic differences in leaf secondary metabolism, plant hormones and yield under alone and combined stress of drought and salinity in cotton genotypes

Abstract: Drought and salinity stress highly affect the plant growth and production around the world. Secondary metabolites play a main role in adaptation to the environment and in overcoming stress conditions. In order to investigate the effect of drought and salinity, alone or in combination, on secondary metabolism‐related enzyme activities, plant hormones and yield parameters, a greenhouse pot experiment was conducted using two cotton genotypes Zhongmian 23 (salt tolerant) and Zhongmian 41 (salt sensitive). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 61 publications
3
39
0
1
Order By: Relevance
“…GWAS analyses of BNPP are relatively rare, especially under salt stress. Our studies showed that salt stress can lead to a significant decrease in boll number per plant, which was consistent with previous reports [40,50], indicating that boll number is the first limiting factor for increasing cotton lint yield under stress environments. We also found that the number of repeated QTLs associated with BNPP was low under different salt conditions, implying a complex regulatory mechanism for BNPP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…GWAS analyses of BNPP are relatively rare, especially under salt stress. Our studies showed that salt stress can lead to a significant decrease in boll number per plant, which was consistent with previous reports [40,50], indicating that boll number is the first limiting factor for increasing cotton lint yield under stress environments. We also found that the number of repeated QTLs associated with BNPP was low under different salt conditions, implying a complex regulatory mechanism for BNPP.…”
Section: Discussionsupporting
confidence: 93%
“…Cotton yield decreases under salt stress. Previous studies have reported that SBW, LP and BNPP are remarkably decreased under salt stress conditions [40][41][42]. In the present study, we selected four different field soil salt environments with two year replicates to investigate the lint yield components of cotton accessions.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS analysis on BNPP are relatively rare, especially under salt stress. Our studies showed that salt stress can lead to a significant decrease in boll number per plant which was consistent with previous reports [46,52], indicating that boll number is the first limiting factor for increasing cotton lint yield under stress environments. We also found the overlapped QTLs associated with BNPP was few under different salt conditions, implying a complex regulatory mechanism for BNPP production.…”
Section: Discussionsupporting
confidence: 93%
“…Excavating elite alleles that can Cotton yield decreases under salt stress. The previous studies reported that SBW, LP and BNPP remarkably decreased under salt stress [46][47][48]. In present study, we selected four different field soil salt environments with two year replicates to investigate the lint yield components of cotton accessions.…”
Section: Discussionmentioning
confidence: 97%
“…Salt stress causes cellular water loss and produces ROS, which disrupt biochemical reactions [48, 49]. Chitinase is generally a useful target related to plant reactions against salt stress, and its increased expression level confers a higher salt resistance to plants [50, 51]. Similarly, increased expression of phospholipase D1 decreases osmotic stress [52].…”
Section: Discussionmentioning
confidence: 99%